The Impact of Perspective Change As a Cognitive Reappraisal Strategy on Affect: A Systematic Review - Wallace-Hadrill, Sophie M. A.; Kamboj, Sunjeev K. (Frontiers in Psychology, 2016)
The strategic or deliberate adoption of a cognitively distanced, third-person perspective is proposed to adaptively regulate emotions. However, studies of psychological disorders suggest spontaneous adoption of a third-person perspective reflects counter-productive avoidance. Here we review studies that investigate the deliberate adoption of a third- or first-person vantage perspective and its impact on affect in healthy people, ‘sub-clinical’ populations and those with psychological disorders. A systematic search was conducted across four databases. After exclusion criteria were applied, 38 studies were identified that investigated the impact of both imagery and verbal instructions designed to encourage adoption of a third-person perspective on self-reported affect. The identified studies examined a variety of outcomes related to recalling memories, imagining scenarios and mood induction. These were associated with specific negative emotions or mood states (dysthymia/sadness, anxiety, anger), mixed or neutral affect autobiographical memories, and self-conscious affect (e.g. guilt). Engaging a third-person perspective was generally associated with a reduction in the intensity of positive and negative affect. Studies that included measures of semantic change, suggested that this is a key mediator in reduction of affect following perspective change. Strategically adopting a “distanced,” third-person perspective is linked to a reduction in affect intensity across valence, but in addition has the potential to introduce new information which regulates emotion via semantic change. Such reappraisal distinguishes deliberate adoption of a distanced perspective from the habitual and/or spontaneous shift in perspective that occurs in psychopathology.